Utilization of Video-Based Learning Media to Improve Digital Literacy of Junior High School Physical Education Teachers - Aryanti, Silvi; Destriana, Destriana; Ramadhan, Anugrah Agung; Anisa, Anisa; Qibtiyah, Maryatul (Asosiasi Profesi Multimedia Indonesia, 2025)
Background: Digital literacy is crucial in the Industry 4.0 era. The use of technology in education involves various learning media. One such learning medium is video, which is more engaging than conventional media by presenting images, audio, and explanatory sentences, thereby improving digital literacy.Aims: The purpose of this community service activity is to improve the digital literacy of middle school physical education teachers in Palembang by utilizing video-based learning media, thereby actively engaging teachers. The scope of this paper is to introduce digital concepts and literacy for physical education teachers, provide guidance on the use of video for basic badminton footwork techniques, and evaluate the implementation of these activities.Methods: This community service activity uses a participatory approach, namely a combination of training and mentoring for physical education teachers.Results: The pre-test and post-test results showed an 80% increase. This indicates that physical education teachers are interested in participating in community service activities, have improved knowledge of video-based learning media, and are able to effectively utilize it.Conclusion: Researchers found that community service activities were successfully implemented with active participant involvement. The activities included the presentation of video-based learning media on badminton footwork techniques.